A Protestant church in Communist China Moore Memorial Church Shanghai 1949-1989 - Keating, John Craig William (Lanham : Lehigh University Press, 2012)
This book is the first ever case study of a single inner-city church in China, tracing the church & rsquo;s struggles with the ups and downs of Chinese politics. Concentrating on the little known Mao era and utilising many interviews and personal documents, the author explores the relationship between Church and State, shedding valuable light on the often volatile interplay between politics and religion...
Acknowledgements; Spelling and Terminology; Chapter 1. Introduction; Chapter 2. The Pre-Communist Era (1887-1949); Chapter 3. Adjusting to the New Regime (1949-51); Chapter 4. The Call to Re-Align (1950-58); Chapter 5. A Church Under Pressure (1958-66); Photospread; Chapter 6. A Church Closed (1966-79); Chapter 7. Re-Opening (1979-89); Chapter 8. The Church Today (1989- ); Chapter 9. Conclusions; Bibliography; Appendix 1: Timeline of Major Events Relevant to MMC; Appendix 2: Biographies of Key People Connected to MMC; Appendix 3: Glossary of Chinese Names and Terms; Index.
Includes index.
Description based on print version record.
Keywords: Church and state -- China; Moore Memorial Church (Shanghai, China); Protestant churches -- China -- Shanghai -- History -- 20th century; Religion; RELIGION / Christianity / Protestant; Electronic books